EXAMINING THE VALUE RELEVANCE OF ACCOUNTING INFORMATION: EVIDENCE FROM NAIROBI STOCK EXCHANGE (NSE) - Mehreteab Yonas Kiflom; Zhang Rui; Lijuan Xiao; Asif Jam Muhammad Farooq; Lukman Jimoh Rahim (Gusau Journal of Accounting and Finance)
Prior studies indicate that with the transition of economy from industrial to a technology-driven service-oriented economy, the usefulness of accounting numbers, especially earnings, has reduced. This is shown by the obscurity of the link?between market stock prices in accounting figures, especially earnings. Based on his perspective, this study examines the extent of stock price movement explained by the change in key accounting metrics using companies listed on the Nairobi Securities Exchange. The sample comprises 56 listed companies across 23 sectors from 2016 to 2023. Using a panel data fixed effects regression, we examine the impacts of key accounting metrics on market share prices. We find that both?(lnEPS ? = 0.137; p < 0.05) and (lnDPS ? = 0.331; p < 0.01) have statistically significant positive relationships with share prices in the market (lnMSP). In contrast, lnOCF (? = 0.01, p <?0.1) and lnTA (? = 0.013, p < 0.1) have positive but insignificant impact effects. The R-squared of the model is 0.471, indicating that the four accounting variables explain 47.1 % of the movement in stock price. The findings align with the Dividend Signaling Theory and the Bird-in-Hand Theory. Additionally, the findings show the existence of a weak-form efficient market in the Nairobi Stock Exchange. Generally,?the study confirms the persistence of accounting information’s value relevance in equity investments in Kenya.